Le bâtiment des archives départementales du Val-de-Marne : un équipement du Nouveau Créteil de l’agence Badani et Roux-Dorlut - Franca Malservisi (In Situ)
Three modern public facilities constitute an essential contribution by the architects Badani and Roux-Dorlut to the landscape of the New Creteil: the hotel of the prefecture, the courthouse and the building of the departmental archives. Information about the construction of these buildings in the early 1970s is now necessary to ensure their sustainability and to respond to their evolving needs. An historical survey of the archives building, originally part of a global reflection on the improvement of thermal performance, allows for a retrospective look at many constructive and formal aspects typical of such architectural expressions of modernity. The design phase of the project confirms the inventiveness of the architectural duo’s research into sculptural forms and the close links between these three structures at Créteil. The archives building project explores a functional organisation that separates a low concrete volume, for the administrative offices and the reception of the public, and the two silos for archive storage. Thanks to the intelligent use of contrast between aesthetics such as rounded versus sharp edges, deactivated concrete versus curtain walls, and blind volumes versus transparent splitting, the building keeps us searching and hoping for more, which is surprising for a public facility of such modest dimensions. The evolution of the project also explains some aspects of the technical problems observed. The transformation of urban development during construction and the evolution of the surrounding environment appear as the main reasons for the relatively weak relationship between the building and its surrounding public space. Finally, the conflicting history of Luxalon aluminium strip cladding provides an overview of the hazards inherent in the adoption of new materials and techniques. Through the understanding of the interactions between formal innovation and constructive experimentation, emanate the recommendations that ensure the maintenance and enhancement of this architectural heritage.